Analisis Tingkat Literasi Politik Mahasiswa Fakultas Ushuluddin Adab dan Dakwah Universitas Islam Negeri Mahmud Yunus Batusangkar - Habibur Rahman (Politik Islam, 2023)
This study focuses on knowing the political literacy abilities of Ushuluddin Adab and Da'wah Faculty students. This type of research is descriptive with a quantitative approach with a questionnaire instrument. Data collection was carried out by distributing questionnaires to 91 respondents from the Usuluddin Adab and Da'wah Faculty students. The type of research that the researchers used was descriptive quantitative analysis. The research questionnaire was tested for validity and reliability using the Cronbach's Alpha technique with the help of IBM SPSS V25. The researcher uses the political evaluation criteria as a theory which is then used as the basis for the discussion. The results show that the ability of Ushuluddin Adab and Da'wah Faculty students can be said to be good. From the research conducted in the field, it can be concluded that the ability of political literacy when viewed by students of the Ushuluddin Adab and Da'wah Faculty when viewed from the knowledge indicator is at a moderate level with a percentage of (69.2%). While the political literacy of fuad students from the attitude indicator is classified as high with a percentage of (79.1%) and in terms of literacy, the fuad students from the aspect of expertise (skil) are classified as moderate with a percentage of (63.7%)